2017
DOI: 10.1080/08039488.2017.1382569
|View full text |Cite
|
Sign up to set email alerts
|

Children exposed to a natural disaster: psychological consequences eight years after 2004 tsunami

Abstract: The negative psychological impact on children and adolescents can still be present eight years post-disaster and seems to have association with the type of exposure; loss, physical presence and subjective experience. It is important for clinicians, who meet young adults seeking help, to be conscious about the impact as long as eight years post disaster and to be aware of possible clinical implications associated with severity of exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
1
15
0
5
Order By: Relevance
“…Many types of natural and manmade disasters are known to be correlated with anxiety, depression, irritability, nightmares and even the posttraumatic stress disorders (PTSD) among children. Previous studies have dealt mainly with the associations of childhood stress with earthquakes (Fujiwara et al 2017;Lieber 2017;Spinelli et al 2020;Uemoto et al 2012) hurricanes (Lonigan et al 1994), tsunamis (Adebäck, Schulman, and Nilsson 2018;Dyb et al 2011;Irwanto, Faisal, and Zulfa 2015;Juth et al 2015), floods (Martin, Felton, and Cole 2016) and radiation hazards (Lieber 2017).…”
Section: Disaster and Stress Of Childrenmentioning
confidence: 99%
“…Many types of natural and manmade disasters are known to be correlated with anxiety, depression, irritability, nightmares and even the posttraumatic stress disorders (PTSD) among children. Previous studies have dealt mainly with the associations of childhood stress with earthquakes (Fujiwara et al 2017;Lieber 2017;Spinelli et al 2020;Uemoto et al 2012) hurricanes (Lonigan et al 1994), tsunamis (Adebäck, Schulman, and Nilsson 2018;Dyb et al 2011;Irwanto, Faisal, and Zulfa 2015;Juth et al 2015), floods (Martin, Felton, and Cole 2016) and radiation hazards (Lieber 2017).…”
Section: Disaster and Stress Of Childrenmentioning
confidence: 99%
“…Further, two separate studies of childhood tsunami survivors indicated that psychological symptoms have the potential to persist from months to years after the disaster. However, in both studies, the severity and type of exposure were associated with persistence of mood symptoms 15,31 . Longer‐term impacts have also been observed in studies of childhood survivors of tornadoes, hurricanes, and in utero heat exposure 29,34,35 .…”
Section: Potential For Long‐term Effectsmentioning
confidence: 77%
“…However, in both studies, the severity and type of exposure were associated with persistence of mood symptoms. 15,31 Longer-term impacts have also been observed in studies of childhood survivors of tornadoes, hurricanes, and in utero heat exposure. 29,34,35 It is important to note that despite the substantial body of evidence intimating the potential for negative long-term effects of childhood EWE exposure, there are both protective and risk factors, such as resiliency, coping skills, and support networks that influence symptom and recovery trajectories.…”
Section: Potential For Long-term Effectsmentioning
confidence: 98%
See 1 more Smart Citation
“…Of those 255 (42%) answered a questionnaire that was sent out in 2013, and 210 young adults who had been in an affected area were included in different studies. Those included were divided into four exposure groups in a previous study (Adebäck, Schulman, & Nilsson, 2018) based on the type of exposure they experienced. Those who were least exposed were placed in exposure group one: they had simply been present on the beach or had simply seen the wave.…”
Section: Methodsmentioning
confidence: 99%